A new system of sperm cryopreservation: evaluation of survival, motility, DNA oxidation, and mitochondrial activity. (27th March 2019) - Pabón, D.; Meseguer, M.; Sevillano, G.; Cobo, A.; Romero, J. L.; Remohí, J.; de los Santos, M. J.
Abstract: Background: Sperm vitrification (V) is a method for cryopreservation, without the use of conventional cryoprotectants, by plunging the sperm suspension directly into liquid nitrogen (LN25). Objective: This study aimed to compare the new system of V with conventional freezing (CF) protocol using fresh spermatozoa as reference (C). Material and methods: Prospective cohort study. A total of 47 sperm samples from men attending the infertility clinic at Instituto Valenciano de Infertilidad Valencia. The sperm V solution was 0.3 M trehalose–sucrose and plunged directly in liquid nitrogen in microdroplets of 5–10 lL, using a new system collector of V. Sperm viability indicators such as sperm motility, vitality rates, mitochondrial function, and sperm DNA oxidation were assessed before and after cryopreservation. Sperm motility and vitality analysis were performed according to published guidelines of the World Health Organization (WHO, 2010). Mitochondrial function was evaluated using JC‐1 (fluorescent cationic dye, 5, 50, 6, 60‐tetrachloro‐1‐10, 3, 30‐tetraethyl‐benzamidazolocarbocyanin iodide). Sperm DNA oxidation was determined using a fluorescent assay (Oxy‐DNA test) for the detection of 8‐oxoguanine. The evaluation was carried out before and after cryopreservation using flow cytometry. Statistical analysis was performed using ANOVA and chi‐square test, and p < 0.05 was considered statistically significant. Result(s): Sperm parameters, including progressive motility, total motility, and viability, observed after cryopreservation were as follows: C = 74.9% [1] 12.3, CF = 27.2% [1] 8.4, V = 42.3% [1] 9.3, p < 0.001; C = 90.1 [1] 6.8, CF = 42.0 [1] 12.9, V = 61.4 [1] 11.8, p < 0.001; C = 90.0% [1] 7.4, CF = 42.5% [1] 14.6, V = 70.9% [1] 6.5, p < 0.001, respectively. Regarding Oxy‐DNA and mitochondrial activity, they were significantly affected in both groups (V and CF) when compared to the control group. Discussion: The sperm V and CF have negative impact on sperm parameters as well as DNA integrity and mitochondrial activity. However, sperm V presented improved sperm motility recovery, similar levels of DNA oxidation, and, moreover, a slightly increase in mitochondrial activity when compared to the conventional method. Conclusion(s): V as an optimal protocol for sperm cryopreservation.